2022
DOI: 10.3390/nu14030542
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of Global Research Productivity on Vitamin D and Bone Metabolism (2001–2020): Learn from the Past to Plan Future

Abstract: Vitamin D has long been known for preserving bone and non-skeletal health. Despite its magnitude of impact, scarce literature has explored the evolution of the relevant published literature. This study aimed at evaluating the trends and performance of Vitamin D and bone metabolism-related publications (2001–2020). All pertinent English language 16,887 articles were searched and extracted from the Web of Science (WoS) database and “R-Bibliometrix” was used for comprehensive analysis. Around 60,149 authors contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 54 publications
2
13
0
3
Order By: Relevance
“…This also indirectly reflected the overall favorable development of research in this field. Our results are consistent with previous studies ( 17 , 20 ). Their findings suggested that in recent years, the research hotspot for vitamin D has changed significantly from bone metabolism to other fields, such as neuroscience, cardiovascular diseases, cancer, as well as immune-related diseases.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This also indirectly reflected the overall favorable development of research in this field. Our results are consistent with previous studies ( 17 , 20 ). Their findings suggested that in recent years, the research hotspot for vitamin D has changed significantly from bone metabolism to other fields, such as neuroscience, cardiovascular diseases, cancer, as well as immune-related diseases.…”
Section: Discussionsupporting
confidence: 94%
“…These data indicate that the influence of Chinese academics and research institutions in this field is relatively limited compared to that of developed Western countries. The lack of impact of Chinese scholars may be related to the weak international collaboration ( 17 ). The same situation is present for India.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D 3 (cholecalciferol) is a bioactive substance formed from cholesterol in the human body, and it can also be obtained from food, especially cod liver and other types of oily fish [6]. In the body, cholecalciferol is converted into a hormonally active form -calcitriol (1α,25(OH) 2 D 3 ), and after the formation of a complex with a specific receptor (vitamin D receptor, VDR), it can regulate the expression of more than 1000 genes [7].…”
Section: E X P E R I M E N T a L W O R K S E X P E R I M E N T A L W ...mentioning
confidence: 99%
“…Bibliometric analysis is the timely and comprehensive review of publications during a specific period by analyzing their parameters, such as the number of publications, authors, countries and regions, references, keywords, and so on, which can provide an exhaustive overview of the intellectual landscape and make researchers cast light on the latest research trends ( 12 ). To our knowledge, no bibliometric study has been reported so far at the global level on hepatic glycolipid metabolism .…”
Section: Introductionmentioning
confidence: 99%